Analysis and design of ferro-cement pipes - Nibhondh Theeranartsin; Lee, Seng-Lip; Tongchat Hongladaromp; Australian Government (Bangkok : Asian Institute of Technology, 1973)
The purpose of this research is to study the analysis and design of ferro-cement pipes subjected to design loads specified by ASTM Designation C 76-72. The analysis is carried out by employing cylindrical shell theory with some simplifying assumptions. Various designs for the ferro-cement pipes are considered and compared, in terms of cost and weight, with ordinary reinforced concrete pipes designed for the same load. It was found that ferro-cement pipes with the minimum use of wire mesh, which possess better cracking properties than reinforced concrete pipe, could be designed to yield competitive cost with reinforced concrete pipes of the same diameter.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Pipe, Ferrocement; Pipe, Concrete